Clinical scoring for distinction of bacterial and viral upper respiratory tract infections of children - Mesut Arslan; Ayşegül Elbir Şahin; Osman Gülsever; Hatice Şanlı Güneş; Betül Aslaner Aldemir; Fatih Duran; İrfan Oğuz Şahin (SERNEV, 2017)
Introduction: Upperrespiratory tract infections (URTI) arethe most common infections of childhood.The purpose of our study is to develop a clinical scoring method todistinguish viral and bacterial infections in the patients who were diagnosedwith URTI. Methods: This study was conducted in pediatric 220 patientswith URTI whose ages were between 5 and 15. The previous studies about clinical scoring ofbacterial and nonbacterial URTI were reviewed to determine signs and symptomsto evaluate in our study. These signs,symptoms and throat swab culture results of the patients wererecorded. Results: Throat swab culture were positive at 93 patients(42%). According to this clinic scoring system; fever, painful anteriorservical lymphadenopathy, lack of cough, tonsillar hypertrophy were found to bestatistically significant in terms of predicting bacterial infections.Dysphagia, abdominal pain, headache, lack of conjunctivitis, the absence ofhoarseness and the absence of diarrhea were found to be statisticallyinsignificant. Conclusion: Acording to total score - culture relationship,total score 7 and higher could be considered significant. As a result of ourstudy, we could not develop an effective scoring due to the high number ofparameters, low sensitivity and specifity.